2013
DOI: 10.1080/00324728.2013.856459
|View full text |Cite
|
Sign up to set email alerts
|

The educational gradient in marital disruption: A meta-analysis of European research findings

Abstract: A large number of empirical studies have investigated the effects of women's education on union dissolution in Europe, but results have varied substantially. This paper seeks to assess the relationship between educational attainment and the incidence of marital disruption by systematizing the existing empirical evidence. A quantitative literature review (a meta-analysis) was conducted to investigate the temporal change in the relationship, net of inter-study differences. The results point to a weakening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
108
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 94 publications
11
108
2
4
Order By: Relevance
“…There has been substantial empirical evidence for Goode's model of the diffusion of divorce (Matysiak, Styrc, and Vignoli 2014;Chan and Halpin 2005;Härkönen and Dronkers 2006). In the Spanish case, previous evidence supplied by Martínez-Pastor (2010, 2011), using data from the Fertility, Family and Values Survey (2006), has also shown the declining importance for women of socioeconomic variables such as education and the labour market situation.…”
Section: Introductionmentioning
confidence: 99%
“…There has been substantial empirical evidence for Goode's model of the diffusion of divorce (Matysiak, Styrc, and Vignoli 2014;Chan and Halpin 2005;Härkönen and Dronkers 2006). In the Spanish case, previous evidence supplied by Martínez-Pastor (2010, 2011), using data from the Fertility, Family and Values Survey (2006), has also shown the declining importance for women of socioeconomic variables such as education and the labour market situation.…”
Section: Introductionmentioning
confidence: 99%
“…It is derived from this assertion that controlling for economic characteristics, the educational gradient of divorce should be negative. As is discussed in Matysiak et al (2011), highly educated women might have lower divorce risks because they have better social, communication and cognitive skills; and they also experience less marital strain, as they enjoy higher standards of living. For a more thorough discussion on the educational gradient of divorce, see Härkönen and Dronkers (2006) and Matysiak et al (2011).…”
Section: The Share Of Earnings Contributed By the Wifementioning
confidence: 99%
“…However, the association differed by gender attitudes within countries -a higher education was associated with a lower likelihood of divorce in gender-egalitarian societies, but with a higher likelihood of divorce in more gender-traditional countries. In a meta-analysis of fifty-three studies of education and divorce across Europe, Matysiak, Styrc, and Vignoli (2014) found a generally positive socioeconomic gradient in divorce -but with variation across countries -and they note that the relationship between education and divorce has weakened over time as divorce has become more common and as women have increasingly entered the labor force. In a recent paper that conjointly considers union formation and dissolution patterns as linked to socioeconomic status, Perelli-Harris and LyonsAmos (2016) used data across fifteen countries with latent-class analysis to examine partnership trajectories.…”
Section: Families Unequal: Socioeconomic Gradients 33mentioning
confidence: 99%
“…Future research should also analyze contextual mechanisms that may explain why maternal education seems to condition family structure effects differently across outcomes and countries, such as the cross-national variations on the percentage of children in joint physical custody. The two premises underlying the diverging destinies thesis -namely that growing up in a nontraditional family is negatively related to child outcomes and that it is a more common experience for socioeconomically disadvantaged children -have been widely documented across a large body of studies (Amato 2000;Matysiak, Styrc, and Vignoli 2014). A recent update of these trends has shown that the "diverging destinies" thesis remains relevant today (McLanahan and Jacobsen 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation